1995
DOI: 10.1175/1520-0477(1995)076<0655:dotlit>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Droughts of the Late 1980s in the United States as Derived from NOAA Polar-Orbiting Satellite Data

Abstract: Drought is one of the most adverse and powerful weatherrelated disasters that occur every year across a portion of the United States. The consequences of droughts quite often can be devastating. To mitigate these consequences, droughts require careful monitoring. Recently, NOAA's National Environmental Satellite Data and Information Service developed a new Advanced Very High Resolution Radiometer-based vegetation condition index (VCI) that showed good results when it was used for drought detection and tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
346
0
9

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(356 citation statements)
references
References 10 publications
1
346
0
9
Order By: Relevance
“…In the US, these include the Vegetation Drought Response Index (Veg-DRI), which monitors drought conditions for the continental US by combining climate-related variables with satellitederived vegetation condition information obtained using Advanced Very High Resolution Radiometer (AVHRR)-based vegetation indices (Brown, 2010), and the University of Washington Experimental Surface Water Monitor , based on a multi-model monitor employing VIC (Liang et al, 1994), Sacramento Soil Moisture Accounting (SAC-SMA; Burnash, 1995), Community Land Model (CLM; Dai et al, 2003;Lawrence et al, 2011), Catchment (Koster et al, 2000), and Noah (Chen et al, 1996;Ek et al, 2003;Koren et al, 1999) land-surface models (LSMs). Other AVHRR-derived drought indices include the Vegetation Condition Index (VCI), derived from AVHRR Normalized Difference Vegetation Index (NDVI) data and the Temperature Condition Index (TCI), which is calculated using AVHRR thermal data (Kogan, 1990(Kogan, , 1995, as well as the Vegetation Health Index (VHI) which combines the VCI and TCI (Kogan, 1997). Remotely sensed land-surface temperature and vegetation cover information have also been combined within the Atmosphere-Land Exchange Inverse (ALEXI) surface energy balance algorithm (Anderson et al, 1997(Anderson et al, , 2007a to generate an Evaporative Stress Index (ESI), quantifying anomalies in the ratio of actual to potential evapotranspiration (Anderson et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In the US, these include the Vegetation Drought Response Index (Veg-DRI), which monitors drought conditions for the continental US by combining climate-related variables with satellitederived vegetation condition information obtained using Advanced Very High Resolution Radiometer (AVHRR)-based vegetation indices (Brown, 2010), and the University of Washington Experimental Surface Water Monitor , based on a multi-model monitor employing VIC (Liang et al, 1994), Sacramento Soil Moisture Accounting (SAC-SMA; Burnash, 1995), Community Land Model (CLM; Dai et al, 2003;Lawrence et al, 2011), Catchment (Koster et al, 2000), and Noah (Chen et al, 1996;Ek et al, 2003;Koren et al, 1999) land-surface models (LSMs). Other AVHRR-derived drought indices include the Vegetation Condition Index (VCI), derived from AVHRR Normalized Difference Vegetation Index (NDVI) data and the Temperature Condition Index (TCI), which is calculated using AVHRR thermal data (Kogan, 1990(Kogan, , 1995, as well as the Vegetation Health Index (VHI) which combines the VCI and TCI (Kogan, 1997). Remotely sensed land-surface temperature and vegetation cover information have also been combined within the Atmosphere-Land Exchange Inverse (ALEXI) surface energy balance algorithm (Anderson et al, 1997(Anderson et al, , 2007a to generate an Evaporative Stress Index (ESI), quantifying anomalies in the ratio of actual to potential evapotranspiration (Anderson et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to precipitation, the PDSI also needs to use temperature and other local hydrological quantities. It has been found that the PDSI has many significant limitations [e.g., Alley, 1984;Karl and Knight, 1985;Smith et al, 1993;Willeke et al, 1994;Kogan, 1995;McKee et al, 1995;Guttman, 1998] and is not satisfied in the operational monitoring [e.g., Hayes et al, 1999]. Mo and Chelliah [2006] made some modifications to improve the PDSI.…”
Section: Introductionmentioning
confidence: 99%
“…(2) At 100 percent VCI, NDVI j = NDVI max and at zero per cent VCI, NDVI j = NDVI min . According to Kogan (1997), different degrees of drought severity are indicated by VCI below 50 per cent and VCI of 35 per cent is a threshold for extreme drought (Table 3). Based on this the VCI values obtained were reclassified into drought severity as: 50 per cent to 100 per cent, normal to above normal condition (wet); < 50 per cent to 35 per cent, moderate drought; < 35 to 20 per cent severe drought; < 20 per cent to zero per cent very severe drought.…”
Section: Processing Of Vegetation Datamentioning
confidence: 99%